(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Metals and their alloys play a fundamental role in prosthetic dentistry. Despite the development of metal-free technologies, metal structures remain in demand due to their high strength, reliability and durability. The effective use of metallic materials is closely related to the technological processes of their manufacture and processing.